Characterization of the Immune Response Induced by a Commercially Available Inactivated Bluetongue Virus Serotype 1 Vaccine in Sheep - Ana Cristina Pérez de Diego; Pedro José Sánchez-Cordón; Ana Isabel de las Heras; José Manuel Sánchez-Vizcaíno (The Scientific World Journal)
The protective immune response generated by a commercial monovalent inactivated vaccine against bluetongue virus serotype 1 (BTV1) was studied. Five sheep were vaccinated, boost-vaccinated, and then challenged against BTV1 ALG/2006. RT-PCR did not detect viremia at any time during the experiment. Except a temperature increase observed after the initial and boost vaccinations, no clinical signs or lesions were observed. A specific and protective antibody response checked by ELISA was induced after vaccination and boost vaccination. This specific antibody response was associated with a significant increase in B lymphocytes confirmed by flow cytometry, while significant increases were not observed in T lymphocyte subpopulations (CD4+, CD8+, and WC1+), CD25+ regulatory cells, or CD14+ monocytes. After challenge with BTV1, the antibody response was much higher than during the boost vaccination period, and it was associated with a significant increase in B lymphocytes, CD14+ monocytes, CD25+ regulatory cells, and CD8+ cytotoxic T lymphocytes.